Potential Prediction of Acute Biliary Pancreatitis Outcome on Admission. Issue 4 (April 2018) - Papapanagiotou, Angeliki; Sgourakis, George; Peristeraki, Stella; Raptis, Dimitris; Karkoulias, Kyriakos; Tezas, Stergios; Patel, Panna; Papavassiliou, Athanasios G.
Abstract : Objectives: This pilot study aimed to determine the feasibility of serum values of osteonectin, adiponectin, transforming growth factor beta 1, and neurotensin being used in clinical practice to predict the severity of acute pancreatitis. Methods: Blood samples were collected from 45 consecutive newly diagnosed acute pancreatitis patients and 30 matched healthy controls. The 2 groups were matched according to age, sex, weight, height, diabetes, smoking, and alcohol consumption. The aforementioned markers were measured using enzyme-linked immunosorbent assay kits. Results: Characteristics of acute pancreatitis patients and healthy controls were comparable. Osteonectin values differed significantly ( P < 0.0001). Median/lower quartile/upper quartile of osteonectin levels for acute pancreatitis patients and healthy controls were 263.5/110.3/490.36 and 63.2/46.1/87.2 ng/mL, respectively. Two patients died, 1 patient underwent necrosectomy, and 4 patients had a prolonged intensive care unit/hospital stay. Acute Physiology and Chronic Health Evaluation II and Systemic Inflammatory Response Syndrome scores neither predicted serum values of any of the measured substances nor the clinical outcome (need for intervention, prolonged intensive care unit/hospital stay and mortality). Osteonectin was the only independent predictor for clinical outcome ( P = 0.007). Conclusions: Serum osteonectin strongly discriminates healthy individuals from acute pancreatitis patients. Serum osteonectin shows promise in the prediction of the clinical outcome.